THE USE OF TRANSITION SIGNALS IN EFL ACADEMIC WRITING CONTEXT: A CORPUS STUDY - Made Wahyu Mahendra; Ni Putu Ratna Puspita Dewi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
For foreign language learners, especially in university, academic writing is essential. Students are required to analyse, compare, and inform through academic writing. Moreover, when they reach the end of their study, they should write a thesis as part of a requirement to graduate. Thus, thesis writing is a major challenge for students. Halliday and Hassan as cited in Hinkel (2001) emphasise that academic writing should achieve cohesiveness to make it well-constructed and understandable. Transition signal is one of prominent cohesive devices that should be taken into account in academic writing. This study aims to identify students’ problems and tendency in using transition signals in academic writing. The data are gained from university students’ academic writing product which is built in a form of corpus. The data are then analysed by using corpus software (ant conc.3.2.4). Its implication on English Language Teaching (ELT) concerning the teaching of transition signals will also be addressed